Twig Pattern Minimization Based on XML Schema Constraints - Gao, Yuan; Liao, Husheng; Gao, Hongyu (INTERNATIONAL JOURNAL OF COMPUTERS & TECHNOLOGY, 2016)
Twig pattern is one of the core components of XQuery. Twig usually includes redundancy nodes which can be optimized. Schema feature is used to judge whether the node of Twig pattern is redundancy. In this paper, we propose sufficient Schema constraints and specific rules. In this paper, we have designed more determination conditions to optimize, then we will get the most efficient results. By a large number of test case, we finally get the practical limits of minimization.